2009
DOI: 10.3171/2008.11.peds08154
|View full text |Cite
|
Sign up to set email alerts
|

First experiences with an adjustable gravitational valve in childhood hydrocephalus

Abstract: Object The goal of this report was to describe the authors' initial experiences with an adjustable gravity-assisted valve (GAV) called the ProGAV in treating childhood hydrocephalus. Methods The ProGAV was implanted in 53 children (29 boys and 24 girls, median age 7.3 years) with hydrocephalus of various origins. The ProGAV consists of a differential-pressure unit with adjustable opening pressures and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 17 publications
(17 reference statements)
2
15
1
1
Order By: Relevance
“…The 1-year survival rate was 81%, and the overall shunt failure was 16.2%; these findings are in agreement with other recent reports 12,13,23,24) . Seven patients who demonstrated overdrainage had cranial defects when shunt surgery was performed (41%, p = 0.629).…”
Section: Shunt Failures and Complicationssupporting
confidence: 82%
See 1 more Smart Citation
“…The 1-year survival rate was 81%, and the overall shunt failure was 16.2%; these findings are in agreement with other recent reports 12,13,23,24) . Seven patients who demonstrated overdrainage had cranial defects when shunt surgery was performed (41%, p = 0.629).…”
Section: Shunt Failures and Complicationssupporting
confidence: 82%
“…Although much pro- 3,7,8) , but 20% seems to be the rate cited most often 5,27) . Recently, new shunt technologies have been introduced to minimize overdrainage, including the GAV (the concept for which had already been introduced by Hakim in 1975), the programmable valve, and the programmable GAV 9,17,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the feasibility of using this shunt system in an infant population is demonstrated, which has similarly been shown for a general pediatric population. 20,43,48 The use of the gravitational unit of the system to try to counteract severe overdrainage is also well tolerated by infants. Clinical observation has shown that during long-term follow-up, signs and symptoms of overdrainage (e.g., decreased ventricular size on imaging, diminished development of head circumference, and headaches) may develop with the advancing growth and activity of the child.…”
Section: Discussionmentioning
confidence: 99%
“…The ventricular catheter was placed in a frontal precoronal position in all patients to allow the valve to be placed in a strictly vertical position subcutaneously behind the ear. 43 The ventricular catheter was connected to a bur hole reservoir. Antibiotic-impregnated silicon tubes (Bactiseal; Johnson & Johnson) were used for all cases from 2009 on, and the tubes were fixated with nonresorbable ligatures.…”
Section: Progav Systemmentioning
confidence: 99%
“…The chosen resistance of the gravitational unit (vertical position) of the proGAV valve was 20 cm H 2 O. 27 In all patients peritoneal diversion of the CSF was used. In cases in which 2 ventricular catheters were placed the catheters were connected via a Yshaped connector proximal to the single implanted valve.…”
Section: Surgerymentioning
confidence: 99%